Synthesis, Characterization and 3D Micro-Structuring via 2-Photon Polymerization of Poly(glycerol sebacate)-Methacrylate–An Elastomeric Degradable Polymer - Pashneh-Tala, Samand; Owen, Robert; Bahmaee, Hossein; Rekštytė, Sima; Malinauskas, Mangirdas; Claeyssens, Frederik (Frontiers in Physics, 2018)
Poly(glycerol sebacate) (PGS) has been utilised in numerous biomaterial applications over recent years. This elastomeric and rapidly degradable polymer is cytocompatible and suited to various applications in soft tissue engineering and drug delivery. Although PGS is simple to synthesise as an insoluble prepolymer, it requires the application of high temperatures for extended periods of time to produce an insoluble matrix. This places limitations on the processing capabilities of PGS and its possible applications. Here, we present a photocurable form of PGS with improved processing capabilities: PGS-methacrylate (PGS-M). By methacrylating the secondary hydroxyl groups of the glycerol units in the PGS prepolymer chains, the material was rendered photocurable and, in combination with a photoinitiator, crosslinked rapidly on exposure to UV light at ambient temperatures. The polymer’s molecular weight and the degree of methacrylation could be controlled independently and the mechanical properties of the crosslinked material tailored. The polymer also displayed rapid degradation under physiological conditions and cytocompatibility with various primary cell types. As a demonstration of the processing capabilities of PGS-M, µm scale 3D scaffold structures were fabricated using 2-photon polymerisation and used for 3D cell culture. The tunable properties of PGS-M coupled with its enhanced processing capabilities make the polymer an attractive potential biomaterial for various future applications.